Jews and Heretics in the Late Antique and Byzantine Imagination: The Longer View - Cameron, Averil (Henoch, 2022)
The task of this contribution is that of asking how and why negative attitudes to Jews and to heretics were entangled together in early Christian sources and why that assimilation continued at such a late date as Byzantine time. Many different literary genres (from adversus Judaeos dialogues to hagiography, epistolography, and so on) stage conflicting relationships between Jews and Christian and should force us to question their rhetorical strategies even more than the real existence of conflicts between religious communities. The development of heresiology, the identification and condemnation of new heresies in order to define orthodoxy with greater and greater precision, constantly reused the argumentative tools and the violent and aggressive language that polemists had used against the Jews, and kept on tracing the roots of all heresies back to Hellenists and Jews, in such a way to reshape the imagination of Jews.